Power Imbalance in the Network: The Formation Logic of Institutional Barriers to Collaborative Governance at the Grassroots Level (Journal of humanities and social sciences exploratio, 2026)
Collaborative governance at the grassroots level is a crucial measure for advancing the modernization of the social governance system and capacity. However, such collaborative governance faces certain institutional barriers, including distorted implementation and defects within formal institutions, as well as normative gaps and conflicts within informal institutions. These factors lead to difficulties in multi-actor coordination, inefficient resource allocation, and low governance effectiveness. The main causes of these institutional barriers include incomplete laws and policies, enforcement loopholes, unclear division of responsibilities and interests, conflicts, constraints from traditional beliefs and customs, information asymmetry, and trust crises. From the perspective of network power, the formation mechanisms of institutional barriers primarily involve imbalances between management authority and service authority, between resource allocation authority and autonomy, and between administrative authority and self-governance. To overcome these institutional barriers, it is essential to strengthen institutional empowerment by ensuring participation rights and decision-making rights for all governance actors; foster and develop social organizations to enhance grassroots self-governance capacity; and promote the deep integration of information technology with grassroots governance to improve governance effectiveness.